Technology Packages for Reclamation and Development of Wastelands - Sundararaju, R.; Chinnathurai, A. K. (Indian Forester, 1992)
In wasteland afforestations utmost care should he taken for selection of proper species. In areas of poor depth of soil and poor moisture retension application of fertilizers and tank silt/organic manure will increase success. Wrighna tinctoria, Hardwickia binata, Albizia amara will suit well. In social forestry, failure in plantation can be brought down by soil testing and selecting suitable species with some reclamation measures. Experiments in Tamil Nadu indicate that Casuarina performs well in mine spoils. Acacia planifrons, Acacia mellifera and Casuarina junghuniana could be used in drought prone area. Area under severe saline/alkaline problems could be improved by applying Gypsum and fertilizers with drainage facilities. Cassia stamea, Casuarina, Eucalyptus camaldulensis and Azadirachta indica grow well even in such area.